Amado Castro and gender equity in education - Paqueo, Vicente B.; Orbeta, Aniceto C. (The Philippine Review of Business and Economics, 2017)
Amado Castro very early on noticed an emerging gender equity issue in education: males doing worse than females. He made this observation before this showed up in national statistics. He also provided insights into why this trend is happening and what its implications are. More recent research has validated this observation. This paper argues for the need to fine-tune the gender equality advocacy in education in the case of the Philippines. There is a need to probe deeper and beyond the global stereotypical recommendation of promoting the education of girls alone. Failure to pursue win-win strategies to address gender bias in education working against boys could mean the country foregoing valuable opportunities to raise equity and economic returns to its investment in education.